Effects of fluid ingestion on intraocular pressure in normal young Malaysian adults - Yusof @ Alias, Firdaus; Mohammad, Nor Ariza; Rashidi, Nadiah; Megat Basri, Megat Ahmad Fadhil; Hilmi, Mohd Radzi (Universiti Putra Malaysia Press, 2025)
Introduction: Intraocular pressure (IOP) is an important parameter in diagnosing and monitoring glaucoma. IOP is dynamic and its measurement and monitoring is challenging. Water Drinking Test (WDT) is a test to evaluate the fluctuation of IOP due to fluid ingestion. This study aimed to investigate the effect of WDT on IOP in normal young healthy adults. Materials and Methods: Eighty participants were recruited in this prospective study. Comprehensive optometric examination were done including Goldmann application tonometry and visual field (VF) testing. Refractive error were objectively measured using Shin Nippon SLM-500 auto-refractometer. VF testing was done using automated perimetry. All procedures were performed between 08:00 to 12:00 PM, and every 5 minutes for 30 minutes after 1000mls of water. All data were analysed using repeated measures analysis of variance (RM-ANOVA). Results: Immediately after the WDT, the IOP increase to its peak at 10 minute and reducing trend was observed from the peak to the 30 minutes timeline. RM-ANOVA analysis revealed significant changes in IOP measurements between baseline and 30 minutes observation period (P < 0.001). Post hoc comparisons using the Tukey HSD test indicated the changes in IOP between right after drinking to at 10 minutes (mean = 17.8, SD = 2.3) was significant compared to other time intervals (P < 0.001). No significance difference (P = 0.09) in IOP between baseline and 30 minutes. Conclusion: WDT is a meaningful, quicker alternative test in attempting to uncover diurnal IOP characteristics in clinic, thus reducing both time requirements and associated costs.